1995
DOI: 10.1002/ijc.2910610602
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma and use of sunscreens: An EORTC case‐control study in germany, belgium and france

Abstract: Use of sunscreens is widely advocated as a preventive measure against sun-induced skin cancers. However, to date, no epidemiologic study has reported a decreased melanoma risk associated with sunscreen use. We have conducted a case-control study aimed at evaluating the influence of sunscreen use on the occurrence of cutaneous malignant melanoma. In 1991 and 1992, 418 melanoma cases and 438 healthy controls were interviewed in Germany, France and Belgium. The questionnaire used differentiated between regular su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1
4

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(82 citation statements)
references
References 19 publications
3
74
1
4
Order By: Relevance
“…Eight epidemiologic studies have reported that regular use of sunscreens is associated with significantly increased risk of melanoma (19,(47)(48)(49)(50)(51)(52)(53). The association persisted after controlling for the amount of time spent in the sun, skin type, and other predisposing factors, including history of sunburns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight epidemiologic studies have reported that regular use of sunscreens is associated with significantly increased risk of melanoma (19,(47)(48)(49)(50)(51)(52)(53). The association persisted after controlling for the amount of time spent in the sun, skin type, and other predisposing factors, including history of sunburns.…”
Section: Discussionmentioning
confidence: 99%
“…The association persisted after controlling for the amount of time spent in the sun, skin type, and other predisposing factors, including history of sunburns. Five of these studies reported higher risk of melanoma associated with use of sunscreens in both sexes (19,49,50,52,53), while three reported the association in men (47,48,51). Another study reported a higher incidence of nevi, pigmented benign lesions of the epidermis that are associated with increased risk of melanoma, in children whose parents regularly applied sunscreens to the children's skin when outdoors in the sun (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore an unsettling observation that increased sunscreen use has coincided with an increase in skin cancer. Most notably the incidence of melanoma has risen, although the relationship between the effects of sunscreens upon melanoma is hotly debated [1][2][3][4][5][6]. Complicating the traditional concept of photoprotection is our limited understanding of the photochemistry UV filters undergo in the skin.…”
mentioning
confidence: 99%
“…Numerous case-control studies focusing on the effect of sunscreen use and the risk of CM reported contradicting results reaching from a reduced risk, [5][6][7][8] an unchanged risk, 9 to an increased risk in persons using sunscreen. [10][11][12][13][14][15][16][17] Most of these case-control studies were hospitalbased, might not have been controlled comprehensively for exposure to sunlight and skin type and were most likely influenced by recall bias, as they involved melanoma patients. Meta-analyses of studies published recently on the relationship of sunscreen use and the risk of CM could not find any association.…”
mentioning
confidence: 99%